A unique sonographic presentation of prenatal volvulus associated with malrotation. Issue 7 (6th July 2021) - Green, Tamar; Chen, Daniela; Mishael, Tali; Shen, Ori
Abstract: This is a unique case of prenatal diagnosis of bowel malrotation suspected by an abnormal course of the duodenum. Early detection of volvulus was enabled, leading to timely intervention and a favorable outcome. Abstract : This is a unique case of prenatal diagnosis of bowel malrotation suspected by an abnormal course of the duodenum. Early detection of volvulus was enabled, leading to timely intervention and a favorable outcome.